Circulating Markers in Gastroenteropancreatic Neuroendocrine Tumors (GEP NETs) - Massironi, Sara; Spampatti, Matilde Pia; Rossi, Roberta Elisa; Conte, Dario; Ciafardini, Clorinda; Cavalcoli, Federica; Peracchi, Maddalena (IntechOpen, 2012)
None